2007
DOI: 10.2174/156800907781386632
|View full text |Cite
|
Sign up to set email alerts
|

Inducible Nitric Oxide Synthase-Vascular Endothelial Growth Factor Axis: A Potential Target to Inhibit Tumor Angiogenesis by Dietary Agents

Abstract: Human solid tumors remain latent in the absence of angiogenesis since it is a critical process for their further growth and progression. Experimental evidence suggests that targeting tumor angiogenesis may be a novel strategy to check tumor growth and metastases. Recent studies suggest that several bioactive food components can suppress tumor growth by inhibiting angiogenesis. This suppression occurs because of a direct effect on the tumor, as well as a direct effect on vascular endothelial cells. These food c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 101 publications
(151 reference statements)
0
4
0
Order By: Relevance
“…γ-Tocotrienol has been reported to activate the nuclear receptors PXR, which regulates the expression of P-gp encoding gene MDR1 (Zhou et al, 2004). Finally, asiatic acid is a pentacyclic triterpenoid derived from the tropical medicinal plants Centella asiatica and Melaleuca ericifolia (Hsu et al, 2005; Singh and Agarwal, 2007). Several studies have also shown asiatic acid to be cytotoxic in a wide variety of cancer cell lines, including breast cancer, melanoma and myeloma (Hsu et al, 2005), and was reported to have anti-angiogenic and anti-Alzheimer’s activities (Singh and Agarwal, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…γ-Tocotrienol has been reported to activate the nuclear receptors PXR, which regulates the expression of P-gp encoding gene MDR1 (Zhou et al, 2004). Finally, asiatic acid is a pentacyclic triterpenoid derived from the tropical medicinal plants Centella asiatica and Melaleuca ericifolia (Hsu et al, 2005; Singh and Agarwal, 2007). Several studies have also shown asiatic acid to be cytotoxic in a wide variety of cancer cell lines, including breast cancer, melanoma and myeloma (Hsu et al, 2005), and was reported to have anti-angiogenic and anti-Alzheimer’s activities (Singh and Agarwal, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…4A). Additional IHC studies were also carried to determine whether IP6 feeding also affects the expression of inducible nitric oxide synthase (iNOS), an enzyme involved in the production of nitric oxide (NO) which facilitates neo-vascularization and invasion (38). The data indicated that IP6 significantly decreases (31–34%, P <0.001 for both doses) iNOS immunoreactivity scores (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Total ribonucleic acid (RNA) was extracted as previously described. 34 To identify genes that are affected by diabetes with and without insulin treatment, real-time polymerase chain reaction (PCR) was carried out using the rat angiogenesis arrays (Qiagen, USA) using a BioRad IQ5 real-time instrument (BioRad, Hercules, CA) per manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“… 28 32 NO modulates insulin sensitivity, 33 and like PGE 2 , interacts with VEGF to promote endothelial cell proliferation, migration, differentiation, and interaction with the extracellular matrix. 34 …”
Section: Introductionmentioning
confidence: 99%